Making Local Water Planning Gender and Socially Inclusive: Towards Gender Inclusive Water Sector Development - International Centre for Integrated Mountain Development (International Centre for Integrated Mountain Development, 2017)
A crucial natural resource, water plays a multi-faceted role in the lives of rural residents in Nepal. However, climate change threatens to disturb that relationship as variations in temperature, rainfall, and rainfall patterns are affecting water availability. Thus, water scarcity has become an increasingly challenging issue, oftentimes leading to conflict, which leads to excess workloads for everyone. In situations like these, power differentials between men and women as well as different social groups can unduly influence decision-making processes around water.